Determining the effect of centrifugal and electrical forces on the jet behaviors, the nanofiber structure, and morphology. (27th December 2018) - Hosseinian, Hajar; Valipouri, Afsaneh; Hosseini Ravandi, Seyed Abdolkarim; Alirezazadeh, Azam
Abstract : The increasing demand for nanofibers production has led to the rapid growth of the usage of electro‐centrifugal spinning (ECS) systems especially in recent years. Besides the rapid developments, fabrication of novel fibrous materials with novel techniques is still under investigation. Polyvinylepyrrolidone (PVP) is one of the multifunctional materials, which has attracted scientific interests to be employed in a variety of advanced applications. The main objective of the present study was therefore to explore the effects of essential parameters involved in fabrication of PVP nanofibers via an ECS system. The effects of rotational speed (197‐4051 r/min) and applied voltage (0‐14 kV) on the structural and morphological properties of nanofibers were also investigated. Analyses of the scanning electron microscope (SEM) images were performed with Digimizer and SPSS16.0 software to characterize the diameter distribution of the nanofibers. The degree of crystallinity was evaluated by the X‐ray diffraction method. In order to explain the unexpected results, further investigations were performed on the motion of the jet and flow rate. The results showed that instead of nanofibers, microparticles were formed at lower voltages and rotational speeds. The increase in the applied voltage resulted in a decrease in the minimum rotational speed that is required to form continuous fluid jet. The bending instabilities were changed from whipping to spiraling at the voltages above 10 kV. This resulted in the minimum fiber diameter at a voltage between 6 and 10 kV. Moreover, the applied voltage slightly affected the degree of crystallinity. No significant change was observed in the degree of crystallinity by varying the rotational speed.